Actions of mental health in the Health Family Strategy - Fernanda Barreto Mielke; Agnes Olschowsky (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The changes current from the process of Psychiatric Reform value the territorial attention. Thus the basic care, from the Health Family Strategy, becomes a privileged space in mental health attention. In this study, we have an objective to evaluate the actions of mental health in the Health Family Strategy, from of the professionals in the evaluate process. We want to strengthen the relationship between mental health and basic care, considering the positive experiences in that direction.